The income tax consequences of the clawback of shares in the context of employee share schemes - Keke, Anelisa (Department of Finance and Tax, 2022)
The objective of this dissertation is to examine the income tax consequences of the clawback of shares awarded in terms of employee share schemes in South Africa in terms of the Income Tax Act 58 of 1962 as amended (“the ITA”). The dissertation first examines how section 8C of the ITA would apply in the context of clawback, and concludes that in certain circumstances clawback will postpone the tax vesting date. It then examines the capital gains tax implications of clawback provisions, which hinge on the interpretation of section 8C and the legal nature of clawback respectively. The tax implications of clawback in respect of cash-based payments is another area of focus, and generally clawback will only delay the taxing point if it is framed as a suspensive condition. The tax implications for the employer and employee respectively are then assessed. It concludes that where the employer has claimed a deduction upon settlement, when the award is subsequently clawed back, only the value claimed as a deduction should be included in the employer's income. Where an employee claims a deduction for the amount which is clawed back (where the employer withheld Employees' Tax), a concomitant tax deduction may be available in certain circumstances. Ambiguities in the existing tax law (which may lead to unintended consequences) are then considered, and it is suggested that certain amendments to section 8C may resolve some of the ambiguities. The final chapter summarises the key findings.